Odpowiedzi

Najlepsza Odpowiedź!
2009-12-09T22:13:37+01:00
2009-12-09T22:23:32+01:00
1) x²-2x+3x²+6x=0
4x²+4x=0

Δ=b^2-4ac
Δ=4^2
Δ=8
√Δ = √8=2√2

x1=-b-√Δ/2a
x1=-4-2√2/8
x1=-1-2√2/2

x2=-b+√Δ/2a
x2=-4+2√2/8
x2=-1+2√2/2


2) 3x²-4=4-12x
3x²-4-4+12=0
3x²+12-8=0

Δ=b^2-4ac
Δ=12²-4×3×(-8)
Δ=48
√Δ=√48=12√3

x1=-b-√Δ/2a
x1=-12-√48/6
x1=-6-12√3

x2=-b+√Δ/2a
x2=-12+12√3/6
x2=-6+12√3
2009-12-09T22:28:32+01:00
(3x-2)²=4(1-3x)
9x²-12x+4=4-12x
9x²-12x+4-4+12x=0
9x²=0
x²=-9
sprzeczność.


reszta to jakieś przykłady z kosmosu..;/